Pesan Komunikas Spiritual dalam Ritual Adat Kololi Kie di Kesultanan Ternate - Nabila Husen Alhaddad; Rachmat Effendi (UNISBA Press, 2022)
Abstract. Various cultural traditions in Indonesia related to religious values ​​as well as spiritual values ​​are still the characteristics of each region that are still maintained until now. In North Maluku, precisely in the Ternate Islands, there is a traditional Kololi Kie ritual which is a tradition that has been carried out for a long time by the Sultanate of Ternate. Kololi Kie is a traditional ritual performed by circling Mount Gamalama by boat to visit the sacred tombs of the ancestors who are all over the island. The implementation of the Kololi Kie traditional ritual has important spiritual values ​​and messages for the people of Ternate. Based on this phenomenon, the researcher has several problem formulations, namely: 1) What are the types of spiritual communication messages in the adar kololi kie ritual in the Sultanate of Ternate? 2) What are the forms of traditional Kololi Kie rituals in the Sultanate of Ternate? 3) What is the relationship between the message of spiritual communication and the traditional ritual of Kololi Kie in the Sultanate of Ternate?. The purpose of this study is to find out more about spiritual communication messages in the kololi kie ritual. The research method used by the researcher is explanatory qualitative. With content analysis theory and ethnographic approach. The message of Spiritual Communication in the Kololi Kie traditional ritual is found in the ritual process. The Kololi Kie ritual is a ritual based on Islamic teachings that have been inherited for a long time. Abstrak. Beragam tradisi budaya di Indonesia yang berkaitan dengan nilai keagamaan dan juga nilai spiritual masih menjadi ciri khas masing-masing daerah yang masih dipertahankan hingga sekarang. Di Maluku Utara tepatnya di Kepulauan Ternate, terdapat ritual adat Kololi Kie yang merupakan tradisi yang telah dilaksanakan sejak lama oleh Kesultanan Ternate. Kololi Kie adalah ritual adat yang dilakukan dengan cara mengelilingi Gunung Gamalama menggunakan perahu untuk mengunjungi makam suci para leluhur yang berada di seluruh pulau. Pelaksanaan ritual adat Kololi Kie ini memiliki nilai dan pesan-pesan spiritual yang penting bagi masyarakat ternate. Berdasarkan fenomena tersebut, maka peneliti memiliki beberapa rumusan masalah, yaitu: 1) Apa saja jenis-jenis pesan komunikasi spiritual dalam ritual adar kololi kie di kesultanan ternate? 2) Apa saja bentuk ritual adat kololi kie di kesultanan ternate? 3) Bagaimana hubungan antara pesan komunikasi spiritual dengan ritual adat kololi kie di kesultanan ternate?. Tujuan dari penelitian ini untuk mengetahui lebih jauh mengenai pesan-pesan komunikasi spiritual dalam ritual kololi kie. Metode penelitian yang digunakan peneliti adalah kualitatif eksplanatori. Dengan teori analisis isi dan pendekatan etnografi. Pesan Komunikasi Spiritual dalam ritual adat Kololi Kie ini ditemukan dalam proses ritualnya. Ritual Kololi Kie ini merupakan ritual dengan landasan ajaran islam yang telah diwarisi sejak lama.